The Conquest of Española as a "Structure of Conjuncture". - Stone, Erin W. (Ethnohistory, 2021)
This article delves into the conquest and early years of colonization of Española from the perspective of the "structure of the conjuncture." By doing so it prioritizes the Indigenous perspective of conquest, particularly that of the cacique Guacanagarí, who formed the first alliance with the Spaniards in 1492. The article follows the development of the historic alliance, digging beneath the surface of historical chronicles to reveal Indigenous cosmology and agency throughout the skirmishes and intrigue of colonization. In so doing it shows that during the first years of Caribbean colonization, the Spaniards were not in control as all actors were engaging in a novel environment, the structure of the conjuncture. The situation did change by the early 1500s, but the imprint of the structure of the conjuncture was felt for decades to come.